(untitled) (Research, Society and Development, 2020)
The retroviruses responsible for feline immunodeficiency and feline leukemia are spread around the world, affecting a large number of animals. These diseases are lifelong and manifest when the cat is immunosuppressed, bringing numerous consequences to their health. The correct and early diagnosis helps in the management of both infected and uninfected animals in order to extend the life of these felines with quality. The present work aims to compare two different tests for the diagnosis of these diseases, in order to discuss the reason for the discrepancy between the results, to demonstrate the positive and negative points of each one and to help the clinician to choose the best method to be used in each situation. The immunochromatographic test and PCR was performed in 66 animals living in the city of Mineiros, Goiás, Brazil. Among these, eight animals were positives in the immunochromatographic test and five in the PCR test for diagnosis of FIV. For FeLV, there were only one positive feline on immunochromatography and 38 positives on PCR. With this result, the conclusion is that both tests have their limitations and one should consider the pathogenesis of the agent in order perform the test correctly or associate them.